2010
DOI: 10.1590/s1807-59322010000600008
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Filtration Rate Measured by 51Cr-EDTA Clearance: Evaluation of Captopril-Induced Changes in Hypertensive Patients with and without Renal Artery Stenosis

Abstract: INTRODUCTION:Renal artery stenosis can lead to renovascular hypertension; however, the detection of stenosis alone does not guarantee the presence of renovascular hypertension. Renovascular hypertension depends on activation of the renin-angiotensin system, which can be detected by functional tests such as captopril renal scintigraphy. A method that allows direct measurement of the baseline and post-captopril glomerular filtration rate using chromium-51 labeled ethylenediamine tetraacetic acid (51Cr-EDTA) coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…IRI can be caused by kidney transplants, hypovolemia, cardiogenic shock, and renal vascular diseases25. The effective treatment of AKI should begin at the earliest sign of renal dysfunction, but the current preferred biomarkers of AKI such as plasma creatinine, creatinine clearance (CrCl), glomerular filtration rate (GFR) determined using Inulin or Cr-EDTA67 and blood urea nitrogen (BUN)89 lack specificity and sensitivity as they only rise substantially above the normal levels once renal damage has already occurred.…”
mentioning
confidence: 99%
“…IRI can be caused by kidney transplants, hypovolemia, cardiogenic shock, and renal vascular diseases25. The effective treatment of AKI should begin at the earliest sign of renal dysfunction, but the current preferred biomarkers of AKI such as plasma creatinine, creatinine clearance (CrCl), glomerular filtration rate (GFR) determined using Inulin or Cr-EDTA67 and blood urea nitrogen (BUN)89 lack specificity and sensitivity as they only rise substantially above the normal levels once renal damage has already occurred.…”
mentioning
confidence: 99%
“…It concludes that captopril induced a decrease in the GFR that could be quantitatively measured with 51Cr-EDTA. The reduction is more pronounced in hypertensive patients 52 . The efficacy and tolerability of the fixed combination, amlodipine + enalapril, when compared to amlodipine in the normalization of the diastolic arterial pressure were evaluated in patients with coronary artery disease and systemic arterial hypertension.…”
Section: Clinical Cardiologymentioning
confidence: 87%
“…Hypertension. This is the subject of nine original studies [49][50][51][52][53][54][55][56][57] . A study of the influence of hypertension control upon quality of life in patients with and without complications showed that special care programs with multidisciplinary activities, individualized and personalized assistance, easy access to pharmacological treatment, frequent meetings, and active telephone calls for hypertensive patients significantly ameliorate blood pressure control but do not interfere with the quality of life 49 .…”
Section: Clinical Cardiologymentioning
confidence: 99%
“…e gold standard of GFR measurement is clearance of an ideal filtration marker, that is, one which is freely filtered in the glomerulus and is neither secreted, reabsorbed, synthesised, nor metabolised by the kidney. Gold-standard markers used include inulin and radioactive markers, such as 51 Cr-EDTA [12,22] or 99m Tc-DPTA [23]. However, in most cases, they are expensive, difficult to assay, and require International Journal of Nephrology a continuous infusion.…”
Section: Discussionmentioning
confidence: 99%